Rapid urbanization effects on partial pressure and emission of CO2 in three rivers with different urban intensities - Wei Tang (Elsevier, 2021)
Rapid urbanization has been reported to affect carbon biogeochemical cycle of waterways, contributing to even higher carbon dioxide (CO2) outgassing from rivers to the atmosphere. However, knowledge on the magnitude and extent of the urbanization influence on riverine CO2 dynamics is still limited. In this study, we investigated partial pressure of CO2 (pCO2) and CO2 degassing rate in the surface water of three rivers that drain land areas with varied urban coverages. Field sampling and measurements were conducted in the Taohua, Nan and Puli Rivers in China’s mountainous Three Gorges Reservoir (TGR) area during winter 2018 and summer 2019 to determine the effect of urbanization intensity on riverine CO2 degassing. We found that pCO2 level was significantly higher in the river with increased proportion of urban land. Both pCO2 level and CO2 flux rate of the Taohua River (3872 μatm and 574 mmol m−2 d−1) with the highest urban land coverage were significantly higher than those of the Nan River (1737 μatm and 218 mmol m−2 d−1) and Puli River (1218 μatm and 130 mmol m−2 d−1) that drain less urbanized land areas. No significant seasonal difference in pCO2 was found in these subtropical rivers (2402 ± 1421 vs 2112 ± 1254 μatm in the summer and the winter). Overall, pCO2 was positively correlated with the concentration of chlorophyll-a (Chl-a), nutrients (i.e., TDN and TDP), dissolved organic carbon (DOC) and colony-forming units (CFU), and was negatively correlated with pH and dissolved oxygen (DO). We found that pH and DOC loading were the better parameters for predicting pCO2 in the river draining more urbanized land area, and pH and Chl-a were the better parameters for predicting pCO2 in the river draining less urbanized area. These findings highlight the role that urbanization plays in increasing riverine pCO2 through increasing nutrient and DOC inputs from the drainage basin under urban development.